Tuberculosis of the breast: a rare extra-pulmonary presentation of tuberculosis - Iyonu J Onaghinor; Izuchukwu B Achusi; Olumuyiwa E Ariyo (Journal of Infection in Developing Countries)
Introduction: Breast tuberculosis (TB) is a rare extra-pulmonary presentation of tuberculosis. In the western world, this accounts for less than 0.1% of breast conditions (all breast conditions, not limited to TB or extra-pulmonary TB), but can be up to 3-4% in regions endemic for TB such as in Africa and Asia.